6 YEARS OLD CHILD WITH DENGUE HAEMORRHAGIC FEVER - Hario Tri Hendroko (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Dengue hemorrhagic fever is a severe and sometimes fatal infection which are widely distributed in subtropical and tropical areas of the world. It is a mosquito-borne disease transmitted by Aedes aegypty mosquitoes and caused by the dengue virus. A child, 6 years old, came with fever since 3 days earlier, suddenly and continually. Physical examination found hypotension, narrowed pulse pressure, tachycardia, cool or mottled skin, prolonged capillary refill time, decreased urine output, and torniquet test positif. Laboratorry examination found trombositopenia (94000/mL), increased hematocrit level >20%, dengue serology examination IgM(+) and IgG (+). Patient was diagnosed and treated as dengue hemorrhagic fever grade III. Patient received care imediately andfinally recover without any ongoing problems and complications. The prognosis for patient with dengue hemorrhagic fever grade IIIdepends on how early the condition was detected and how early the patient was treated. [J Agromed Unila 2014; 1(3):244-248]Keywords: dengue hemorrhagic fever, pediatric, torniquet test